Analisis Pendidikan Ekonomi Keluarga Pelaku UMKM di Kabupaten Kepulauan Seribu - Ramdhan Kurniawan; Faridah Iriani (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
Indonesia, which joined the MEA in 2015, supports the development of MSMEs, but on the other hand it also provides intense competition because trade is not limited by region. MSMEs are very important to maintain the stability and resilience of a country's economy. The Thousand Islands only contributed 0.32% (3,735 units) of MSMEs in DKI Jakarta Province. Family economic education is important as a basis for running a business. Parents have a duty as the first place of education for children as the next generation. Important basic tools to form attitudes and patterns of thinking. The method used in this study is a qualitative phenomenon approach. MSME actors acquire thrifty, disciplined and productive attitudes that are instilled from an early age by their parents. Introduction to business and business inheritance in the form of children's participation in business management can provide understanding and generate children's interest in pursuing a business. Parents need to convey information in a calm situation and provide comfort for children to express their opinions.